Діалогізм творчості Макса Фріша - Стернічук, Віта Богданівна (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті розглядається комунікативний аспект творчості Макса Фріша, становлення літературного та епістолярного діалогів, діалогізму художніх творів. Діалогізм творчості Макса Фріша – це елемент текстової та життєвої організації. Інструментом впливу для розв’язання та висвітлення стосунків зі світом автор обрав що-денник. Макс Фріш створив складну діалогічну конструкцію гри із читачем. Високий рівень інтертексту¬аль-ності творчості швейцарського письменника, мозаїчність мислення, автобіографічність, нетрадиційність викла-ду (нагромадження фактів) створюють ефект полілогу авторського Я та суспільства, головного Я-героя та читачів. The article deals with the communicative essence of works Max Frisch, the forming category of epistolary and literature dialogues, dialogic of fiction. Dialogue of creativity by Max Frisch – it is an element of textual and vital organization. The author has chosen diary as an instrument for solving and scoring problems. Max Frisch has created complicated dialogical construction of games with the reader. The high level intertextuality of works by Swiss writer, mosaic structure of thinking, autobiographical, non traditional nature of narration (conglomeration of facts) create the effect of polylogue with author and the society, the main hero and readers. Therefore, we can say with certainty, that, in search of forms and sense of creativity, Max Frisch has created a new genre – genre of «skits polylogue». All the works of the writer is a continuation and addition of previous arguments, it is polylogue of separate mosaics with only one entity. In this connection, the writer addresses the reader with a request to read carefully between the lines, do not miss the details, read in a strictly fixed sequence. Only having the keys to understanding the complex codes of narrative technique Frisch, the reader will be able to find an alternative to the understanding of the author: continue to read on with skill or turn to the works, the biography, letters, etc.
Keywords: комунікація; діалог; творчість; інтертекстуальність; епістолярний діалог; автор; адресат; читач